Development of Promotion Model for Immunization Coronavirus disease 2019 Active vaccination by Community participation in Yangtalat District, Kalasin Province - Kanlayasonti, Prasittichai; Nurnchat, Auttawit; Poltu, Cherdchai (Journal of The Royal Thai Army Nurses, 2023)
This study ware research and development aims to analyze situations and development model for immunization of COVID-19 vaccine in elderly and 7 congenital diseases group (in name call 608 group). the sample was the consenting group and the non-vaccinating group, 175 people equally, totaling 350 people. Tools used was storage form and interview form. Results in pre-development period were coverage rate of vaccine ware in Multiple logistic regression founded Death anxiety and accept vaccine service if public health officer goes to service at home. Development model ware founded: 1) Situation analysis of vaccination data; 2) Community leaders, VHV. integrate work at all villages and vaccination campaigns in community participle. 3) Use village health convention center for working 4) Use motorbike innovation service at house and farms 5) Praise vaccinated person model 6) Report chief and district public health officer. After development founded vaccine coverage (83.2%). Recommendations should practice on participle in community, solve attitudes on vaccine deaths and focus on proactive vaccination in community can be successful.